2017
DOI: 10.4236/me.2017.85053
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Effect of Crude Oil Price Movements on US Stock Market Returns and Volatility

Abstract: From mid-2014 to 2016, oil prices plunged rapidly causing significant volatility in the US and global equity markets. This change in crude oil prices occurred after a significant run up in oil prices three to four years earlier. Each change in the growth trajectory of oil prices affects stock market returns. How and why do oil price shocks affect the expected stock market returns among key sectors of the economy? This paper explores this issue by examining how the magnitude of crude oil price changes affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…The disclosure of this information leads to the prediction by the oil companies about a non-increase in their sales revenue and a higher storage cost, which may not generate abnormal positive returns. This result is in line with those obtained by Hall and Kenjegaliev (2017) and Sonenshine and Cauvel (2017)´s studies. Faced with positive oil supply shocks, these authors do not obtain statistically significant positive CARs.…”
Section: Analysis Of Resultssupporting
confidence: 93%
“…The disclosure of this information leads to the prediction by the oil companies about a non-increase in their sales revenue and a higher storage cost, which may not generate abnormal positive returns. This result is in line with those obtained by Hall and Kenjegaliev (2017) and Sonenshine and Cauvel (2017)´s studies. Faced with positive oil supply shocks, these authors do not obtain statistically significant positive CARs.…”
Section: Analysis Of Resultssupporting
confidence: 93%
“…By applying Vector Autoregression (VAR) models and bivariate Granger causality tests, Feride (2015) showed that both symmetric and positive oil price shocks decrease industrial production, money supply, and imports while the negative oil price shocks increase imports. Sonenshine and Cauvel (2017) explored how the magnitude of crude oil price changes affect the stock market returns and variances of key production, banking and consuming segments of the US economy. They provided explanations for the asymmetric responses to positive and negative oil shocks found in key sectors of the US economy.…”
Section: Literature Reviewmentioning
confidence: 99%